Drugging DNA Damage Repair Pathways for Trinucleotide Repeat Expansion Diseases - Benn, Caroline L.; Gibson, Karl R.; Reynolds, David S. (Journal of Huntington's disease, 2021)
DNA damage repair (DDR) mechanisms have been implicated in a number of neurodegenerative diseases (both genetically determined and sporadic). Consistent with this, recent genome-wide association studies in Huntington’s disease (HD) and other trinucleotide repeat expansion diseases have highlighted genes involved in DDR mechanisms as modifiers for age of onset, rate of progression and somatic instability. At least some clinical genetic modifiers have been shown to have a role in modulating trinucleotide repeat expansion biology and could therefore provide new disease-modifying therapeutic targets. In this review, we focus on key considerations with respect to drug discovery and development using DDR mechanisms as a target for trinucleotide repeat expansion diseases. Six areas are covered with specific reference to DDR and HD: 1) Target identification and validation; 2) Candidate selection including therapeutic modality and delivery; 3) Target drug exposure with particular focus on blood-brain barrier penetration, engagement and expression of pharmacology; 4) Safety; 5) Preclinical models as predictors of therapeutic efficacy; 6) Clinical outcome measures including biomarkers.